MACVIA‐ARIA Sentinel NetworK for allergic rhinitis (MASK‐rhinitis): the new generation guideline implementation. Issue 11 (13th September 2015) - Bousquet, J.; Schunemann, H. J.; Fonseca, J.; Samolinski, B.; Bachert, C.; Canonica, G. W.; Casale, T.; Cruz, A. A.; Demoly, P.; Hellings, P.; Valiulis, A.; Wickman, M.; et al.
Abstract Several unmet needs have been identified in allergic rhinitis: identification of the time of onset of the pollen season, optimal control of rhinitis and comorbidities, patient stratification, multidisciplinary team for integrated care pathways, innovation in clinical trials and, above all, patient empowerment. MASK‐rhinitis (MACVIA‐ARIA Sentinel NetworK for allergic rhinitis) is a simple system centred around the patient which was devised to fill many of these gaps using Information and Communications Technology (ICT) tools and a clinical decision support system (CDSS) based on the most widely used guideline in allergic rhinitis and its asthma comorbidity (ARIA 2015 revision). It is one of the implementation systems of Action Plan B3 of the European Innovation Partnership on Active and Healthy Ageing (EIP on AHA). Three tools are used for the electronic monitoring of allergic diseases: a cell phone‐based daily visual analogue scale (VAS) assessment of disease control, CARAT (Control of Allergic Rhinitis and Asthma Test) and e‐Allergy screening (premedical system of early diagnosis of allergy and asthma based on online tools). These tools are combined with a clinical decision support system (CDSS) and are available in many languages. An e‐CRF and an e‐learning tool complete MASK. MASK is flexible and other tools can be added. It appears to be an advanced, global and integrated ICT answer for many unmet needs in allergic diseases which will improve policies and standards.